ANALYZING SUSTAINABLE DEVELOPMENT OF EUROPEAN FUNDED PROJECTS - POPA, Adina Simona; FARCANE, Nicoleta; BLIDIȘEL, Rodica Gabriela (Annales Universitatis Apulensis Series Oeconomica; Vol 2 No 16 (2014): Annales Universitatis Apulensis Series Oeconomica, 2014)
Sustainable development and gender equality are considered horizontal themes of all programs financed by structural and investments European funds. In the perspective of participation in the achievement of an equitably world economic system, European Union presents a strategy for promoting social development and core worldwide labour standards, where sustainable development is based on economic growth strategies as well as, environmental protection, decent living and working conditions and equitable access to resources. Sustainable development and reduction of disparities between European regions are major objectives at European Union level and are supported through EU strategy and operational programs which finance projects that contribute to achieving EU goals. EU monitors periodically tens of sustainable development indicators (SDI) that are intended to give a comprehensive image of whether the EU has achieved progress towards sustainable development in terms of the objectives and targets defined in the EU Sustainable Development Strategy.  In the present paper we used ex-post and content analyses for investigate the results indicators of the projects funded by Regional Operation Programme in the V-West Region of Romania and highlight if the project sustainability indicators are measures of SD as it is presented in the national and European Sustainable Development Strategy.